An evaluation of healthcare use and child morbidity 4 years after user fee removal in rural Burkina Faso - Zombré, David; De Allegri, Manuela (Maternal and child health journal, 2019)
Objectives: Increasing financial access to healthcare is proposed to being essential for improving child health outcomes, but the available evidence on the relationship between increased access and health remains scarce. Four years after its launch, we evaluated the contextual effect of user fee removal intervention on the probability of an illness occurring and the likelihood of using health services among children under 5. We also explored the potential effect on the inequality in healthcare access. Methods: We used a comparative cross-sectional design based upon household survey data collected years after the intervention onset in one intervention and one comparison district. Propensity scores weighting was used to achieve balance on covariates between the two districts, which was followed by logistic multilevel modelling to estimate average marginal effects (AME). Results: We estimated that there was not a significant difference in the reduced probability of an illness occurring in the intervention district compared to the non-intervention district [AME 4.4; 95% CI 1.0-9.8)]. However, the probability of using health services was 17.2% (95% CI 15.0-26.6) higher among children living in the intervention district relative to the comparison district, which rose to 20.7% (95% CI 9.9-31.5) for severe illness episodes. We detected no significant differences in the probability of health services use according to socio-economic status [χ2 (5) = 12.90, p = 0.61]. Conclusions for Practice: In our study, we found that user fee removal led to a significant increase in the use of health services in the longer term, but it is not adequate by itself to reduce the risk of illness occurrence and socioeconomic inequities in the use of health services.